2022
DOI: 10.3390/gels8110755
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Bio-Based Aerogel and Its Adsorption Properties for Organic Dyes

Abstract: The effective utilization of biomass and the purification of dye wastewater are urgent problems. In this study, a biomass aerogel (CaCO3@starch/polyacrylamide/TEMPO-oxidized nanocellulose, CaCO3@STA/PAM/TOCN) was prepared by combining nanocellulose with starch and introducing calcium carbonate nanoparticles, which exhibited a rich three-dimensional layered porous structure with a very light mass. Starch and nanocellulose can be grafted onto the molecular chain of acrylamide, while calcium carbonate nanopores c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…The structures of TOCNs, PAM and TOCNs/PAM hydrogels were characterized by FT-IR [ 31 ] ( Figure 2 a). PAM hydrogel has an obvious wide absorption peak near 3430 cm −1 [ 32 ], which belongs to the N-H stretching vibration of PAM.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of TOCNs, PAM and TOCNs/PAM hydrogels were characterized by FT-IR [ 31 ] ( Figure 2 a). PAM hydrogel has an obvious wide absorption peak near 3430 cm −1 [ 32 ], which belongs to the N-H stretching vibration of PAM.…”
Section: Resultsmentioning
confidence: 99%
“…This is evident in the second step, and the adsorption capacity slowly increases before levelling off. The SO molecules can then penetrate the pores in the final region, before reaching a steady situation due to the repulsive forces between the free SO molecules in bulk solution and the adsorbed molecules [81]. The results indicated that the maximum uptake capacities were 0.99, 2.13, 3.99, 8.79, 18.87 and 24.73 mg/g for the 10, 25, 50, 100, 200 and 300 mg/L Safranin O solutions, respectively.…”
Section: Effect Of Contact Time and Initial Dye Concentrationmentioning
confidence: 99%
“…Adsorption methods are described in the Supplementary Materials. The adsorption processes and mechanisms are explained via kinetic, isothermal, and thermodynamic modeling fits and combinations [29,30].…”
Section: Characterizationmentioning
confidence: 99%